Advantages of “Life Curve” Mobile Application: An Easier Alternate of Paper Partograph - Begum, Ferdousi; Tanvir, Md Sahariar Hossain; Hasan, Md Jahid (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: The WHO approved paper Partograph is a time tested tool for monitoring the progression of labour to reduce life-threatening complications during labour as well as maternal mortality and morbidity. However, inept manpower for recording and interpreting data, chance of retrograde plotting and limited scope of distance monitoring have become a significant barriers to use this tool. The ‘Life Curve’, an Android Apps, is put forward as an easier alternate of the paper partograph. Objective: To see the advantages of the ‘life curve mobile application’: an Android apps which support any Android operating system. It is a new tool based on WHO partograph to monitor the progression of labor with automatically generated interpretation. Early warning and alarm system is included here for creating an opportunity of early referral and intervention. Method: A cross sectional study was conducted in Department of Gynaecology and Obstetrics, Sir Salimullah Medical College & Mirford Hospital from December 2016 to May 2017 on 30 mothers admitted with labour pain. Labor and all other parameters were recorded and monitored by using “life curve” mobile application along with paper partograph. The research protocol including the ethical clearance was approved by Bangladesh Medical Research Council. It is part of the feasibility study of the “life Curve” mobile application. Results: Mean age of the subjects was 25.9±5.7 yrs, mean gestational age 39.6±.9 wks, and 83% had vaginal delivery. The apps is easy to fill up, automatically generates graph, interesting to work with, provides timely automated reminder to evaluate the parturient, generates digital color coded warning figures, sends automated text message to the supervisor in abnormal situation. The performance parameters were scored in a 1-5 scale. For comparing the advantages of using these two partographs, nine features were compared with a total score of 45. Total score for live curve has 42.7 and that for paper postograph was 19.52 the difference is highly significant (p=.001). The mean±SD score of life curve (4.74±.52) was statistically significantly higher than that of paper partograph (2.17±1.18): p<.0002. Conclusions: The life curve mobile application is found to be a easier tool for monitoring of labour with many advantages; and can be used as an alternative of paper partograph. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 84-89